FUNCTIONING OF THE OCCUPATIONAL HEALTH AND SAFETY SYSTEM IN UKRAINIAN INDUSTRY - NESTER, ANATOLIY; YAKOVYSHYNA, TETIANA; MITIUK, LIUDMYLA; СHOLOVSKIJ , ROMAN (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article analyzes the current state of functioning of the system of labor protection and life safety in the Ukrainian industry. Given the high level of occupational injuries and occupational diseases, the issues of ensuring labor safety are of particular relevance. The author analyzes the regulatory framework in the field of labor protection, organizational mechanisms for implementing state policy, and the activities of enterprises aimed at creating safe working conditions.Particular attention is paid to assessing the effectiveness of the existing occupational safety and health management systems at enterprises in various industries. The author identifies the main problems that impede the effective implementation of safety measures, including: outdated material and technical base, insufficient safety culture among employees, formal approach to occupational safety and health training, and weak control by supervisory authorities.The article emphasizes the importance of preventive measures, staff training, and the use of modern technologies and personal protective equipment. Special attention is paid to the problems of implementing labor safety in martial law. Conclusions are drawn regarding the need for an integrated approach to ensuring safe working conditions and strengthening the safety culture in the industry.The paper also highlights positive examples of the implementation of modern approaches to risk management, automated hazard monitoring systems and innovative technologies to improve safety at work. The author suggests ways to improve the national occupational safety and health system, in particular through modernization of legislation, strengthening of employers' liability, introduction of digital tools for recording violations and creation of a single information space on occupational safety and health.The results of the study can be used in the formation of strategic decisions of the state policy, in the development of programs for the professional development of occupational safety specialists, as well as in the practical activities of enterprises to improve working conditions and reduce the risk of occupational injuries.
Keywords: martial law; life safety; working conditions; industry; personal protection